Evaluating a patient's request for life-prolonging treatment: an ethical framework - Winkler, Eva C. (Journal of medical ethics, 2012)
Contrary to the widespread concern about over-treatment at the end of life, today, patient preferences for palliative care at the end of life are frequently respected. However, ethically challenging situations in the current healthcare climate are, instead, situations in which a competent patient requests active treatment with the goal of life-prolongation while the physician suggests best supportive care only. The argument of futility has often been used to justify unilateral decisions made by physicians to withhold or withdraw life-sustaining treatment. However, we argue that neither the concept of futility nor that of patient autonomy alone is apt for resolving situations in which physicians are confronted with patients' requests for active treatment. Instead, we integrate the relevant arguments that have been put forward in the academic discussion about ‘futile’ treatment into an ethical algorithm with five guiding questions: (1) Is there a chance that medical intervention will be effective in achieving the patient's treatment goal? (2) How does the physician evaluate the expected benefit and the potential harm of the treatment? (3) Does the patient understand his or her medical situation? (4) Does the patient prefer receiving treatment after evaluating the benefit-harm ratio and the costs? (5) Does the treatment require many resources? This algorithm shall facilitate approaching patients' requests for treatments deemed futile by the physician in a systematic way, and responding to these requests in an ethically appropriate manner. It thereby adds substantive considerations to the current procedural approaches of conflict resolution in order to improve decision making among physicians, patients and families.